Respuesta :
2x-y=10
2x-2y=4
take the first equation an put Y by itself
y=2x-10
then plug y into the next equation
2x-2(2x-10)=4
2x-4x+20=4
-2x=-16
x=8
Now take your x and plug it into the y equation
y=2x - 10
y= 2(8) -10
y=6
x=8, y=6
2x-2y=4
take the first equation an put Y by itself
y=2x-10
then plug y into the next equation
2x-2(2x-10)=4
2x-4x+20=4
-2x=-16
x=8
Now take your x and plug it into the y equation
y=2x - 10
y= 2(8) -10
y=6
x=8, y=6
x=8, y=6 is the solution.
How to solve the equation?
By using substitution method, we get
2x - y = 10
2x - 2y = 4
Take the first equation an put Y by itself
y = 2x - 10
then plug y into the next equation
2x - 2(2x - 10) = 4
2x - 4x + 20 = 4
-2x = -16
x = 8
Now take your x and plug it into the y equation
y = 2x - 10
y= 2(8) -10
y = 6
x=8, y=6
What is substitution in the formula?
Substitution means replacing the variables (letters) in an algebraic expression with their numerical values. We can then work out the total value of the expression.
Learn more about Substitution here: https://brainly.com/question/261468
#SPJ2